Karakteristik Fisik dan Kimia Edible Film Maizena dengan Penambahan Ekstrak Kayu Secang (Caesalpinia Sappan L.) - Ayudianty, Laras; Dewi, Yohana Sutiknyawati Kusuma; Priyono, Suko (Agriculture Faculty, 2024)
The purpose of this research was to obtain the concentration of secang wood extract that produces the best physcochemical characteristics of maizena edible fim. This study used randomized block design (RBN) with one factor and five replications. The factor of this study was the addition of secang wood extract into maizena edible film which consisted of five levels, namely s0 (0%); s1 (1%); s2 (3%); s3 (5%); and s4 (7%). Analysis of physical and chemical characteristics include thickness, solubility, water holding capacity, antioxidant activity, and total flavonoid compound. The best edible film was selected by De Garmo test. The result showed that 7% of secang wood concentration made the best physcochemical characteristics of maizena edible film with 0,154 mm of thickness, 43,253% of solubility, 4,111 (g/g) of Water Holding Capacity (WHC), 96,485% of antioxidant activity, 252,727 mg QE/g extract of total flavonoid compound.